2021
DOI: 10.5603/njo.a2021.0068
|View full text |Cite
|
Sign up to set email alerts
|

The scope of complementary and alternative medicine in Poland

Abstract: Introduction.Complementary and alternative medicine (CAM) is widely used by patients. The most frequent CAM users are patients with cancer, but patients with other chronic diseases also utilize these methods. Materials and methods. Data on the use of CAM were obtained from Google searches. For each specific search term, the first three Google pages were analyzed.Results. The analysis included 91 CAM institutions matching the inclusion criteria. The most common anticancer services were intravenous vitamin C inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Despite this widespread presence of IVNT marketing, universities or conferences were seldom listed as a source of knowledge on intravenous infusions. These findings confirm previous reports which showed that the market for alternative and complementary services is doing well in Poland [5,13,16]. One in five of our respondents had a patient who used IVNTs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite this widespread presence of IVNT marketing, universities or conferences were seldom listed as a source of knowledge on intravenous infusions. These findings confirm previous reports which showed that the market for alternative and complementary services is doing well in Poland [5,13,16]. One in five of our respondents had a patient who used IVNTs.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is worth noting that commercial infusions and injections are poorly studied in terms of both efficacy and safety [5,[10][11][12]. To date, there are few publications on their benefits, and all those that exist are anecdotal or lack scientific rigour [2,13]. In some cases, the use of IVNTs has been described as having negative or even fatal effects [1,2,7,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perdyan et al analyzed 91 institutions offering alternative therapies that most often concern rheumatological, neoplastic, and chronic diseases [5]. Most institutions offered both drug therapies and therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The growing popularity and heterogeneity of CAM methods make them an important issue for patient-doctor relations in Poland and other Central European countries [4]. A recent study from Poland demonstrated that an astonishing number of CAM practices offered to manage multiple entities [5].…”
Section: Introductionmentioning
confidence: 99%